2007
DOI: 10.1139/y07-001
|View full text |Cite
|
Sign up to set email alerts
|

Circulating stromal osteonectin-positive progenitor cells and stenotic coronary atherosclerosisThis paper is one of a selection of papers published in this Special Issue, entitled The Cellular and Molecular Basis of Cardiovascular Dysfunction, Dhalla 70th Birthday Tribute.

Abstract: The level of circulating stromal progenitor cells carrying osteonectin (ON), a marker of osteogenic differentiation, was evaluated by flow cytometry in blood of patients with coronary artery disease (CAD). Ninety-nine patients with CAD were included into the study. Coronary angiography of all patients showed critical stenosis of at least 2 coronary arteries or their major branches. The control groups included 8 patients without CAD and 19 healthy volunteers. In control patients, no lesions of the coronary bed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The results of proteomic studies indicated high level of stromal stem cell marker osteonectin in the blood of CA patients, which was in line with published data [1,[6][7][8][9]. High level of osteonectin-positive cells was suggested as an indicator of the presence and progress of atherosclerotic involvement of the vessels in humans [1].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The results of proteomic studies indicated high level of stromal stem cell marker osteonectin in the blood of CA patients, which was in line with published data [1,[6][7][8][9]. High level of osteonectin-positive cells was suggested as an indicator of the presence and progress of atherosclerotic involvement of the vessels in humans [1].…”
Section: Resultssupporting
confidence: 87%
“…Presumably, cells proliferating in the vascular intima are of bone marrow origin, and bone marrow colony-forming stem cells of hemopoietic and stromal differentiation lineages penetrate into the vascular intima in sites of lipid concentration and development of atherosclerotic foci [1,6,12]. CD34, highly glycosylated type 1 transmembrane pro tein (sialomucin) is a marker of hemopoietic stem cells, while stromal stem cells carry on their surface osteonectin, a non-collagen bone tissue glycoprotein selectively binding calcium and phosphorus salts to collagen.…”
mentioning
confidence: 99%
“…Recent studies have been suggested that SPARC, such as OSN, osteopontin, and osteoprotegerin, presumably can play an important role in not only CHF, but in atherogenesis also [14] , [15] . The animal models give evidence that OSN levels directly correlate with increased mortality post-MI due to increased rupture rate [16] .…”
Section: Discussionmentioning
confidence: 99%
“…The levels of circulating stromal progenitor cells (Gabbasov et al 2007) and polymorphonuclear leukocytes were measured in blood collected upon coronary angiography. A patient was considered to have an 'in-stent restenosis' when stenosis occurred in the vascular segment (inside and (or) 5 mm distally or proximally to the stent) reducing the lumen diameter by at least 50%.…”
Section: Patientsmentioning
confidence: 99%
“…Stromal colony-forming stem cells were identified in peripheral blood and intima of atheromatous blood vessels of CAD patients (Soboleva et al 1994). Stromal progenitor cells with osteonectin, a marker of osteogenic differentiation, circulate in peripheral blood of CAD patients (Gabbasov et al 2007). It was suggested that the development of an atherosclerotic plaque in the vascular wall is not a local but a systemic process that probably involves bone marrow, blood, and vascular intima.…”
Section: Figmentioning
confidence: 99%